Crescimento e produção do Capim Tifton 85 em condições de irrigação deficitária - Silva, Anita Cristina Costa da (2014)
This work had as objective to evaluate the effect of deficitary irrigation on growth and production of Tifton 85, irrigated by center pivot with five different water depths. The experiment was conducted on a farm producing hay in Bom Despacho, state of Minas Gerais. A randomized complete block design was used, with three replications and five irrigation depths (28%, 42%, 57%, 71% and 85% of Kc values proposed by Allen et al. (1998)). The cycle was 73 days long. Production of pasture, leaf/stem ratio, sward height, dead material, leaf area index (LAI), leaf area ratio (LAR), leaf weight ratio (LWR), specific leaf area (SLA), raw protein (RP), crude fiber, neutral detergent fiber (NDF), acid detergent fiber content (ADF), total digestible nutrients (TDN) were evaluated. The samples to estimate the yield, growth and quality of Tifton 85 were collected when the cut forage for hay production was performed. A frame 0.25 m2 was used to collect the sample to determine the production, leaf/stem ratio and dead material. The leaves were completely cut at soil surface three times in each plot. Height was measured with a millimeter ruler and the aid of a sheet of acetate. To determine the LAI, LAR, PWR and SLA samples were collected from each plot and stored in plastic bags with moist paper towels aiming to conserve fresh material for later use in a leaf area meter. Samples were taken to the laboratory for determination of raw protein, crude fiber, NDF, ADF and TDN cut over 7 cm in each plot and stored in paper bags for later drying in a forced air oven at 65°C for 72 hours. Differences in the production of Tifton 85 were noticed, being the highest production (6,126.35 kg.ha-1) obtained with the application of water depths equivalent to 71%Kc. However there was no difference in height, leaf/stem ratio, dead material, LAI, LAR, LWR and SLA. Regarding the quality of Tifton 85, only raw protein varied as function of varying water depths, with the highest content (10.38%) achieved with the lowest depths applied (28%Kc).